The 2nd European Carotid Surgery Trial (ECST-2): rationale and protocol for a randomised clinical trial comparing immediate revascularisation versus optimised medical therapy alone in patients with symptomatic and asymptomatic carotid stenosis at low to intermediate risk of stroke - Cheng, Suk Fun; van Velzen, Twan J.; Gregson, John; Richards, Toby; Jäger, Hans Rolf; Simister, Robert; Kooi, M. Eline; de Borst, Gert J.; Pizzini, Francesca B.; Nederkoorn, Paul J.; Brown, Martin M.; Bonati, Leo H. (Current controlled trials in cardiovascular medicine, 2022)
Background Carotid endarterectomy is currently recommended for patients with recently symptomatic carotid stenosis ≥50%, based on randomised trials conducted 30 years ago. Several factors such as carotid plaque ulceration, age and associated comorbidities might influence the risk-benefit ratio of carotid revascularisation. A model developed in previous trials that calculates the future risk of stroke based on these features can be used to stratify patients into low, intermediate or high risk. Since the original trials, medical treatment has improved significantly. Our hypothesis is that patients with carotid stenosis ≥50% associated with a low to intermediate risk of stroke will not benefit from additional carotid revascularisation when treated with optimised medical therapy. We also hypothesise that prediction of future risk of stroke in individual patients with carotid stenosis can be improved using the results of magnetic resonance imaging (MRI) of the carotid plaque. Methods Patients are randomised between immediate revascularisation plus OMT versus OMT alone. Suitable patients are those with asymptomatic or symptomatic carotid stenosis ≥50% with an estimated 5-year risk of stroke of <20%, as calculated using the Carotid Artery Risk score. MRI of the brain at baseline and during follow-up will be used as a blinded measure to assess the incidence of silent infarction and haemorrhage, while carotid plaque MRI at baseline will be used to investigate the hypotheses that plaque characteristics determine future stroke risk and help identify a subgroup of patients that will benefit from revascularisation. An initial analysis will be conducted after recruitment of 320 patients with baseline MRI and a minimum of 2 years of follow-up, to provide data to inform the design and sample size for a continuation or re-launch of the study. The primary outcome measure of this initial analysis is the combined 2-year rate of any clinically manifest stroke, new cerebral infarct on MRI, myocardial infarction or periprocedural death. Discussion ECST-2 will provide new data on the efficacy of modern optimal medical therapy alone versus added carotid revascularisation in patients with carotid stenosis at low to intermediate risk of future stroke selected by individualised risk assessment. We anticipate that the results of baseline brain and carotid plaque MRI will provide data to improve the prediction of the risk of stroke and the effect of treatment in patients with carotid stenosis. Trial registration ISRCTN registry ISRCTN97744893 . Registered on 05 July 2012